EFFECT OF THE BALANCED AND NANO-COMPOSITE NPK FERTILIZER ON THE VITALITY OF THE EARTHWORM Octolasion cyanieum AND ITS EFFECT ON THE HISTOLOGICAL COMPOSITION OF THE MIDDLE OF THE BODY (Nativa, 2024)
ABSTRACT: This study was conducted to determine the effects of earthworm breeding O. cyanieum for 7, 14, 21, and 28 days in soil treated with concentrations of 800, 1000, 1500, and 2000 mg kg-1 of balanced NPK compound fertilizer and balanced NPK nano-compound fertilizer at concentrations of 30, 60, 120, and 240 mg kg-1, in addition to the control treatment. It was found that the weight and relative growth rate of earthworms decreased with increasing concentrations of fertilizers. The highest significant decrease in weight (0.257 g) and relative growth rate (40.34%) was observed at a concentration of 1500 mg kg-1 of balanced NPK compound fertilizer. Meanwhile, the highest decrease in worm weight (0.225 g) and relative growth rate (86.31%) was observed at a concentration of 240 mg kg-1 of balanced NPK nano-compound fertilizer. Fertilizers also affected the protein content in the earthworms, which differed significantly from the control treatment for both fertilizers. In addition, the fertilizers affect the histological structure of the body, with clear disruption in the epithelium of the body, layers of circular and longitudinal muscle, the lining of the intestine, especially the typhlosole.Keywords: chemical fertilizer; nano fertilizer; earthworm vitality. Efeito do fertilizante npk balanceado e nanocomposto na vitalidade da minhoca octolasion cyanieum e seu efeito na composição histológica do meio do corpo RESUMO: Este estudo foi conduzido para determinar os efeitos da criação de minhocas O. cyanieum por 7, 14, 21 e 28 dias em solo tratado com concentrações de 800, 1000, 1500 e 2000 mg kg-1 de solo de fertilizante composto NPK balanceado (20-20-20) e fertilizante nanocomposto NPK balanceado (20-20-20) nas concentrações de 30, 60, 120 e 240 mg kg-1 de solo, além do tratamento testemunha. O estudo mostrou que os fertilizantes químicos tiveram impacto sobre a vitalidade dessas minhocas, pois o peso e a taxa de crescimento relativo das minhocas diminuíram com o aumento das concentrações de fertilizantes. A maior queda significativa no peso (0,257 g) e na taxa de crescimento relativo (40,34%) foi observada na concentração de 1500 mg kg-1 de solo do fertilizante composto NPK balanceado. Já a maior redução no peso (0,225 g) e na taxa de crescimento relativo (86,31%) da minhoca foi observada na concentração de 240 mg kg-1 de solo do fertilizante nanocomposto NPK balanceado. Além disso, os tratamentos acima tiveram impacto no teor de proteína dos corpos das minhocas, que diferiu significativamente do tratamento controle, para ambos os tipos de fertilizantes. O estudo mostrou o impacto do fertilizante nas estruturas dos tecidos das minhocas, com clara ruptura na camada da pele e nas camadas musculares circulares e longitudinais abaixo dela, bem como um claro efeito no revestimento intestinal, especialmente o tiflosole.Palavras-chave: fertilizante químico; nano fertilizante; vitalidade da minhoca.